Adaptation and evolution of institutions and governance in community‐based conservation. Issue 1 (5th January 2021) - Salerno, Jonathan; Romulo, Chelsie; Galvin, Kathleen A; Brooks, Jeremy; Mupeta‐Muyamwa, Patricia; Glew, Louise
Abstract: Within conservation science and practice, community‐based conservation (CBC) includes policy and management interventions incorporating engagement or participation of local communities and resource users. Evidence across scales points to the importance of supporting local actors and management institutions for better social and ecological outcomes of CBC interventions. However, the institutional and governance processes underlying CBC outcomes remain poorly understood, specifically how institutions respond to opportunities and constraints posed by CBC. In response, this special issue of Conservation Science & Practice solicited contributions investigating adaptation and evolution of institutions and governance in CBC. In this paper, we introduce the special issue and its 13 contributions, representing cases from Africa, Asia, and the Americas across organizational scales and resource systems. We assess the state of knowledge of CBC, identify common themes and lessons learned, and suggest future priorities for research and practice.